Respuestas
Respuesta dada por:
2
Resolver.
3w² + 17 + 10 = 0
3w² + 27 = 0
3w² = -27
w² = - 27/3
w² = - 9 Tiene como solucion 2 raices imaginarias.
w = ± √-9
w = ± √(9 * -1)
w = ± √9 * √-1 Pero √-1 = i
w = ± √9 i
w =√9 i
w = 3i
o
w = - √9 i
w = - 3i
Solucion.
(3i , - 3i)
3w² + 17 + 10 = 0
3w² + 27 = 0
3w² = -27
w² = - 27/3
w² = - 9 Tiene como solucion 2 raices imaginarias.
w = ± √-9
w = ± √(9 * -1)
w = ± √9 * √-1 Pero √-1 = i
w = ± √9 i
w =√9 i
w = 3i
o
w = - √9 i
w = - 3i
Solucion.
(3i , - 3i)
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años